(untitled) (Mustansiria Dental Journal, 2018)
To determine the most common chief complaints of chronic periodontitis patients to assess the public awareness about this disease symptoms, their distribution among males & females and their correlation with age and some of periodontal parameters (PLI & PPD). Chief complaints of 1115 (641 males & 474 females) chronic periodontitis patients attending the College of Dentistry/ University of Baghdad seeking treatment. The age range was from 23 to 67 years; the mean age was 46.1. The patients divided according to age groups & according to gender. The majority of patients expressing symptoms of chronic periodontitis were mainly between 40 and 60 years old. A highly significant difference between males and females in referral and bleeding (P value= 0.001), a significant difference in mobility, altered gingival appearance, and pain (P value= 0.004, 0.022, and 0.002 respectively); the other chief complaints (pathologic tooth migration and malodor) showed no significant differences between the two groups (males & females)(P value= 0.909, and 0.872). The highest complaint was bleeding (about 31%) followed by referred patients (19.6%), while the malodor was the least reported chief complaints (5.5%). An obvious correlation between chief complaints and age with PPD and PLI for all chief complaints groups. This study showed that there is an ignorance of the nature of periodontal diseases on a community level which calls for more education programs to be carried out by dental team members concerning the proper oral hygiene measures instruction and motivation to reverse or at least minimize the effect of periodontal disease(s).